Platform Session – Electromyography: Nerve ultrasound for the identification of treatment-responsive chronic neuropathies without nerve conduction abnormalities. (May 2018) - Herraets, Ingrid; Goedee, Stephan; Telleman, Johan; van Asseldonk, Thies; van der Pol, Ludo; Visser, Leo; van den Berg, Leonard
Abstract : Introduction: We aimed to determine whether nerve ultrasound can improve detection of potentially treatable chronic inflammatory neuropathies in patients that have normal nerve conduction study (NCS). Diagnostic consensus criteria for inflammatory neuropathies primarily rely on NCS results that indicate multifocal demyelination. However, additional supportive criteria are developed to identify these treatable inflammatory neuropathies. In this study we examined the additional value of sonography in the detection of treatable inflammatory neuropathies. Methods: We analysed 240 incident patients with clinical suspicion of chronic inflammatory neuropathy; work-up consisted of routine ancillary investigations recommended in the diagnostic consensus guidelines and a standardized sonographic protocol assessing arm nerves and brachial plexus. All patients without any demyelinating features on NCS, but with sonographic abnormalities fitting inflammatory neuropathy and a clinical phenotype totally compatible with chronic inflammatory demyelinating polyneuropathy (CIDP), Lewis Sumner Syndrome (LSS), or multifocal motor neuropathy (MMN), received standard treatment with IVIg. Treatment effect was evaluated by routine clinical examination and hand grip or myometry. Results: We found 17 patients (7%) with a clinical phenotype compatible with CIDP (n = 10), LSS (n = 1) and MMN (n = 6, with 3 positive for anti-GM1 auto-antibodies), sonographic nerve enlargement of proximal median nerve segments and/or cervical (nerve) roots, yet negative NCS (2 only axonal loss, 15 normal). An abnormal MRI of brachial plexus was found in 9/17 patients (53%) and an elevated protein content of cerebrospinal fluid in 9/17 patients (53%). All 17 patients showed objective improvement on IVIG treatment. Conclusion: Our study suggests that nerve ultrasound may help to improve detection of treatment-responsive chronic neuropathies, even in patients not fulfilling the diagnostic NCS and other supportive criteria, including MRI of the brachial plexus. Therefore, future revisions of the diagnostic consensus criteria may include sonography as complementary technique to NCS and MRI.